2000
DOI: 10.1111/j.1348-0421.2000.tb02537.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tryptophan‐1 in Hemolytic and Phospholipase C Activities of Clostridium perfringens Alpha‐Toxin

Abstract: Replacement of the Trp-1 in Clostridium perfringens alpha-toxin with tyrosine caused no effect on hemolytic and phospholipase C (PLC) activities or on binding to the zinc ion, but that of the residue with alanine, glycine and histidine led to drastic decreases in these activities and a significant reduction in binding to the zinc ion. The hemolytic and PLC activities of W1H and W1A were significantly increased by the preincubation of these variant toxins with zinc ions, but the preincubation of W1G with the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The overall charasteristics of clostridial phospholipases, including those of Csp presented here, suggest that phospholipase-producing clostridia possess phospholipases which are similar to each other but unique to the species with respect to structure and function. Nagahama et al (15)(16)(17)(18) and Guillouard et al (7) investigated the roles of amino acid residues of Cpa by site-directed mutagenesis and reported that W1, H68, H126, H136, H148, and E152 were essential for zinc binding, D56 and T74 were required for catalitic activity, and D130 and T272 were required for maintainance of structure. All these residues are Ϫ2 anti-His tag Cpa titer) of His tag Cpa-immunized mice were 6 (n ϭ 2), 9 (n ϭ 2), 10 (n ϭ 1), and 12 (n ϭ 1).…”
Section: Discussionmentioning
confidence: 99%
“…The overall charasteristics of clostridial phospholipases, including those of Csp presented here, suggest that phospholipase-producing clostridia possess phospholipases which are similar to each other but unique to the species with respect to structure and function. Nagahama et al (15)(16)(17)(18) and Guillouard et al (7) investigated the roles of amino acid residues of Cpa by site-directed mutagenesis and reported that W1, H68, H126, H136, H148, and E152 were essential for zinc binding, D56 and T74 were required for catalitic activity, and D130 and T272 were required for maintainance of structure. All these residues are Ϫ2 anti-His tag Cpa titer) of His tag Cpa-immunized mice were 6 (n ϭ 2), 9 (n ϭ 2), 10 (n ϭ 1), and 12 (n ϭ 1).…”
Section: Discussionmentioning
confidence: 99%
“…one zinc ion essential for the catalytic site of the toxin, and the peptide bond between Trp-1 and Asp-2, and the His-11 bind another zinc ion (10,11,14). Kameyama et al (7) reported that the His-148 residue is important for activities of the toxin.…”
mentioning
confidence: 99%